Effect of basic washing parameters on the chemical composition of empty fruit bunches during washing pretreatment: A detailed experimental, pilot, and kinetic study. (November 2021) - Singhal, Abhishek; Goossens, Maria; Konttinen, Jukka; Joronen, Tero
Graphical abstract: Highlights: Effect of washing time, temperature, and S:L ratio were studied in-detail. Upto 98% Cl, 80% S, 77% K, 67% ash, and 63% N removal was seen after washing. High time and temperature values shows much lower fouling and corrosion propensity. Leaching of ash, K, Cl, N, and S follows second-order kinetics. Washing for 10 min at 50 °C with 1:15 S:L ratio is recommended for EFB. Abstract: The present study aimed to evaluate the effect of basic washing parameters on the chemical composition of empty fruit bunches of oil palm (EFB) and to determine the optimal parameters for large-scale applications of washing pre-treatment. Three basic washing parameters were studied in detail: washing duration, temperature, and solid/liquid (S:L) ratio. The leaching kinetics of ash and troubling elements such as K, Cl, N, and S were also evaluated with respect to washing time. About 82–98% Cl, 64–80% S, 38–77% K, 34–67% ash, and 24–63% N removal was noted after washing EFB, which follows a second-order leaching kinetics on increasing washing duration. Two pilot washing tests were also conducted to evaluate the effectiveness of the pre-treatment on a large scale, which showed similar trends as the laboratory results. The recommended EFB washing conditions for large-scale applications are 10 min washing with a 1:15 S:L ratio at 50 °C.